Pendampingan Labelisasi Halal Pada UMKM Jamaah Mushola At-Taqwa Mojoroto, Kota Kediri Dalam Meningkatkan Pendapatan. - Soimah, Zakiyatus; Moch. Basit Aulawi; Indriya Inayati (LP3M IAIFA Kediri, 2025)
This community service program involves providing assistance for halal labeling/certification for MSMEs owned by members of the At-Taqwa Mushola congregation, with the aim of increasing the income of MSME entrepreneurs. Using the Asset-Based Community Development (ABCD) approach, the assistance process includes raising awareness about the importance of halal certification, helping with the preparation of required documents, and offering direct support throughout the certification process. This program has led to greater awareness of the importance of halal labeling. In addition, the products of the At-Taqwa Mushola MSMEs have become more marketable and competitive, resulting in increased income for the entrepreneurs.